Implementasi Restorative Justice dalam Sistem Peradilan Pidana Indonesia dalam Tinjauan Keadilan Substantif - Ismawanto Somantri (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The Restorative Justice process constitutes an alternative mechanism for resolving criminal cases outside the court by involving offenders, victims, and relevant stakeholders to reach a fair and recovery-oriented agreement. However, in practice, its implementation still faces challenges, including the dominance of a retributive paradigm among law enforcement officials, fragmented and non-integrated regulations, and the potential risk of re-victimization of victims. This study employs a normative juridical method through literature review with qualitative analysis. The findings indicate that the implementation of Restorative Justice in the Indonesian criminal justice system reflects a shift from a retributive paradigm toward a restorative approach focused on recovery, in line with the principle of substantive justice. Its legal basis is regulated through internal regulations of the police (Perpol 8/2021), the prosecution service (Perja 15/2020), and the Supreme Court (PERMA 1/2024). Strengthening the legal umbrella, training officials, and empowering the role of the community to realize substantive justice that is oriented towards recovery are the solutions.